Traditional Chinese medicine compounds modulate signaling pathways to improve cardiac-related pathology - Zhang, Luwen; Wang, Wei; Liu, Xincan; Yan, Kuipo; Li, Qiang; Li, Ming; Li, Chunying; Li, Yanxin; Chen, Lei (Frontiers in Pharmacology, 2025)
Cardiovascular disease poses a significant risk to human health and remains the leading cause of illness and death globally, with its incidence continuing to rise. The intricate pathophysiological mechanisms of CVDs include inflammation, oxidative stress, autophagy, and myocardial fibrosis. In light of these underlying mechanisms, traditional Chinese medicine (TCM) and its constituents have demonstrated distinct advantages in managing CVDs. By exerting synergistic effects across multiple components and targets, traditional Chinese medicine can modulate the inflammatory response, mitigate oxidative stress, regulate excessive autophagy, and enhance myocardial fibrosis repair. This article reviews the latest advancements in understanding how TCM compounds regulate signaling pathways involved in the treatment of CVDs.